Multiple Phosphorylations of SR Protein SRSF3 and Its Binding to m6A Reader YTHDC1 in Human Cells - Takanori Tatsuno; Yasuhito Ishigaki (Cells, 2022)
N6-methyladenosine (m6A) is a well-known RNA modification and has various functions with its binding proteins. Nuclear m6A reader protein YTHDC1 plays a significant role in RNA metabolism including some non-coding RNA such as LINE or circRNA. It is also known to regulate mRNA splicing through recruiting SRSF3 to the targeted mRNAs, which then mediates export of YTHDC1-bound RNA to the cytoplasm. Additionally, it has been indicated that SRSF3 binding to YHTDC1 may be mediated by its dephosphorylated status. However, their binding mechanism, including the positions of dephosphorylated residues of SRSF3, has not been sufficiently investigated. Thus, we explored the mechanism of interaction between SRSF3 and YTHDC1 in human cells. We used co-immunoprecipitation to examine the binding of YTHDC1/SRSF3 through their N- and C-terminal amino-acid residues. Furthermore, dephosphorylation-mimic serine to alanine mutants of SRSF3 indicated the position of phosphorylated residues. Cumulatively, our results demonstrate that YTHDC1 binding to SRSF3 is regulated by not only hypo-phosphorylated residues of arginine/serine-rich (RS) domain of SRSF3 but also other parts of SRSF3 via YTHDC1 N- or C-terminal residues. Our results contribute to the understanding of the complex mechanism of binding between SR protein SRSF3 and the m6A reader YTHDC1 to regulate the expression of mRNA and non-coding RNAs.